Properties Enhancement Of Propionylated Kenaf Fiber Reinforced Vinyl Ester Composites With The Addition Of Bionanocarbon - Mistar, Eka Marya (2023)
The use of biomass and its waste has been extensively applied in biocomposite applications. This study deals with the utilization of bionanocarbon from oil palm shell (OPS) in vinyl ester composites reinforced by unmodified and propionylated kenaf fibers.